“All the world’s a stage” – The Spatial Value of Destination DJ Videos - Stankov, Uglješa; Carmer, Adam B.; Vujičić, Miroslav D.; Kennell, James; Lazić, Lazar; Kalinić, Časlav; Masliković, Dejan; Jovanović, Slobodan (Geographica Pannonica, 2024)
This exploratory article analyze the contemporary trend in the music and event industry of organizing and filming electronic dance music (EDM) events at tourist destinations. These videos featuring DJ sets in attractive locations, referred to as destination DJ videos (DDJVs), accumulate a substantial number of views on social media platforms, primarily YouTube. Due to their widespread popularity, they represent an untapped source of online media content, holding potential for broader industry utilization and academic analysis of their spatial value, understood as an addition to the typically considered social, cultural, and economic values of music events. DDJVs combine the popularity of a music genre, an artist, a music streaming platform, and the destination featured in the video, offering various perspectives and approaches for assessing and evaluating them within the domain of tourism. The presence of datasets encompassing DDJVs stands as a noteworthy and substantial resource for novel academic explorations within the sphere of tourism research, expanding the scope of visual studies in tourism. Moreover, DDJVs hold the potential to serve as valuable and pragmatic instruments for fostering innovation in the field of destination marketing. This exploratory study provides an early evaluation of research directions for DDJVs.
Keywords: electronic dance music; spatial value; destination marketing; destination management; social media analysis